IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF STRUCTURAL APPROACH NUMBERED HEADS TOGETHER TO IMPROVE STUDENTS’ MATHEMATICS ACHIEVEMENT IN CLASS VIII.6 SMP NEGERI 16 PEKANBARU - Habib Abdullah; Atma Murni; Rini Dian Anggraini (Jurnal Prinsip Pendidikan Matematika, 2020)
This research was conducted because there are still many student learning outcomes that score below the value minimum mastery criteria (KBM) with a percentage of 10,34 % who achieve the minimum mastery criteria on the associating build flat side space of learning mathematics of class student VIII.6 SMP Negeri 16 Pekanbaru. This research aims to improve the learning process and mathematics learning outcomes by Cooperative learning structured approach Numbered Heads Together. The Classroom Action Research with two cycle, conducted in class VIII.6 SMP Negeri 16 Pekanbaru in the second semester of the 2018/2019 academic year. Research subject as many as 29 students. The research instrument consists of learning devices and instrument data collectors. The learning device consists of Syllabus, Lesson Plan and Worksheet. While The instrument data collector consists of observation sheet and math achievement test. The observation sheet obtained by qualitative descriptive while the test of mathematics learning outcomes obtained by analyzed statistically. The process of learning mathematics in cycle I to cycle II has increased. Percentage of students that reach KBM increase from the basic score, test I, and test II. The number of students who reach Minimum Mastery Criteria on basic score, daily test I and daily test II are respectively (10,34 %), (17,24%) and (48,27 %). The conclusion of this research is application of the Cooperative learning structured approach Numbered Heads Together can improve learning process and increase mathematics learning outcomes from the students at class VIII.6 SMP Negeri 16 Pekanbaru in the second semester academic years 2018/2019.